2003
DOI: 10.1016/s0887-6177(03)00022-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits among patients with late-onset minor and major depression

Abstract: Cognitive ability of minor depressed patients (N=28), major depressed patients (N=26) and healthy elderly (N=38) was examined cross-sectionally to determine if cognitive abilities of patients with late-onset depression decrease with increasing severity of disease and if cognitive scores for minor depressed patients fall between those of healthy elderly and major depressed patients. A pooled within-group principal component analysis of cognitive test scores identified five components, three of which showed sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
1
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(119 citation statements)
references
References 77 publications
7
97
1
14
Order By: Relevance
“…Executive dysfunction, including disturbances in response inhibition and initiation as well as perseveration have been reported in late-life depression (Elderkin-Thompson et al, 2003;Lockwood et al, 2002;Nebes et al, 2001). Studies of cognitive response to psychopharmacological treatment of late-life depression indicate that executive function deficits persist after remission of geriatric depression (Nebes et al, 2003;Butters et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Executive dysfunction, including disturbances in response inhibition and initiation as well as perseveration have been reported in late-life depression (Elderkin-Thompson et al, 2003;Lockwood et al, 2002;Nebes et al, 2001). Studies of cognitive response to psychopharmacological treatment of late-life depression indicate that executive function deficits persist after remission of geriatric depression (Nebes et al, 2003;Butters et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that the working memory performance of depressive patients was impaired [2,5,6]. The reason for these inconsistent results is that, in this study, to investigate the working memory performance of depressive patients, firstly, we used pictures instead of words because vocabulary is more closely linked with educational level than pictures; this way, the influence of educational-level factors could be excluded as much as possible; secondly, some studies thought that the working memory performance of depressive patients would diminish along with an increase in task difficulty [5,36,37]. Memory difficulty is one of the main factors that influence memory performance.…”
Section: Discussionmentioning
confidence: 98%
“…Deficits have been reported in domains of attention, language, episodic recall, semantic recall, nonverbal recall, visuospatial/visuoconstruction, working memory, and executive function (Abas et al, 1990;King et al, 1991;Boone et al, 1994;Boone et al, 1995;Lesser et al, 1996;Palmer et al, 1996;Kramer-Ginsberg et al, 1999;Lyness et al, 1999;Yaffe et al, 1999;Nebes et al, 2000;Palsson et al, 2000;Nebes et al, 2001b;Swainson et al, 2001;Elderkin-Thompson et al, 2003;Elderkin-Thompson et al, 2004b). Specifically, they have reduced language fluency (Wolfe et al, 1987;King et al, 1991;Boone et al, 1994;Brown et al, 1994;Palmer et al, 1996), poor processing speed and attentional ability (Boone et al, 1995;Yaffe et al, 1999;Nebes et al, 2000;Palsson et al, 2000;Nebes et al, 2001a), poor inhibition of conflicting information (Palmer et al, 1996), and impaired visuospatial skills (Boone et al, 1994;Boone et al, 1995;Lesser et al, 1996).…”
Section: Depression and Cognitionmentioning
confidence: 99%